Contract Employment as a Worker Discipline Device - Arnab K. Basu; Nancy H. Chau; Vidhya Soundararajan (Institute of Labor Economics (IZA), 2018)
Fixed-term contract employment has increasingly replaced regular open-ended employment as the predominant form of employment notably in developing countries. Guided by factory-level evidence showing nuanced patterns of co-movements of regular and contract wages, we propose a two-tiered task based model with self-enforcing contracts in which firms allocate complex tasks to long term employees at incentive compatible wages, and routine tasks to fixed term employees at acceptable wages. We show that the advent of contract employment effectively lowers the cost of maintaining worker discipline, and demonstrate the conditions under which a positive change in labor demand can end up increasing the share of contract employees. We then argue that the contract employment phenomenon sheds light on two margins of hiring distortions – respectively task assignment and total employment distortions – against which the effectiveness of a suite of oft proposed labor market exibility policies should be assessed.
Keywords: J31; J41; O43; 330; contract employment; two-tiered labor markets; wage polarization